Zwischen Erinnern und Vergessen - Ein Dorf und seine widerständige Vergangenheit - Entner, Brigitte (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2013)
On April 29, 1943, twelve men and one woman were beheaded at the Provincial Court of Vienna. Indictments stated they were all Slovenes. Their guilt? As Carinthian Slovenes they were not obedient to the standards of the Nazi regime. The Reich prosecutor accused them of high treason. While the events, their prehistory and consequences were erased from the historic memory of the German speaking public, different, partly conflicting stories gradually appeared in the Slovene speaking population. Later on, members of the German speaking population and its media started resuming and partly transforming these stories in such a way as to aggravate the conflict potential, immanent to the original stories. The issues concerning possible traitors and deliberately ignoring or distancing from different Resistance activists and groups to whom they had belonged, remains topical even today.
Keywords: Carinthian Slovenes; koroški Slovenci; nacizem; protinacistični odpor; partizani; zeleni kadrovci; Sele; politika spomina